As temperaturas intraurbanas: exemplos do Brasil e de Portugal - Margarete Cristiane de Costa Trindade Amorim; Ana Monteiro (Confins)
The use of thermal infrared images is an important technique to provide qualitative information about the temperature of a city and can greatly contribute to urban planning as they show the impacts of the surface temperature according to the use and occupation of land. This research aims to analyze the differences in summer intra urban temperatures through Landsat 7 satellite thermal images in two medium-sized cities at different latitudes: Porto (Portugal) and Presidente Prudente (Brazil). The results showed that some areas of the city have extremely high surface temperatures contributing to the discomfort.